Konsep Al-Hubb Dalam Al-Qur’an: (Telaah Kitab Tafsir Ruh Al-Ma’ani Karya Imam Al-Alusi) - Avif Alfiyah; Chusnun Nufus (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
Love for Allah, is the highest level of a servant. After a servant reaches hia love for Allah, then there is no longer a level of servitude that is above him, unless he is in the fruit of lofe for Allah, such as longing, serenity and pleasure. Meanwhile, the level of servitude before lofe for Allah is as a prelude to it, such as repentance, patience, astecitism and so on. In this study, the authors use library research (library research). While the discussion uses the thematic method or Mudhu'i interpretation. The author takes classical interpretations such as Imam Al-Alusi because one of the famous commentators of his time, he is one of the mufassir who has a Sufistic style, he also interprets using the tahlili method. What this method stands out for is analyzing the various dimensions contained in the verse to be interpreted. The author also takes the theme of hubb / love, which is still widely discussed at all times.